Non-Linear Biomechanical Evaluation and Comparison in the Assessment of Three Different Piece Dental Implant Systems for the Molar Region: A Finite Element Study - Jesus Alejandro Serrato-Pedrosa; Ignacio Villanueva-Fierro; Rodrigo Arturo Marquet-Rivera; Rosa Alicia Hernández-Vázquez; Salvador Cruz-Lopez; Verónica Loera-Castañeda (Journal of Functional Biomaterials)
The widely available options of different manufacturers in dental implant systems have complicated the selection criteria process for periodontists, necessitating careful consideration of various factors when selecting suitable solutions for individual patient needs. Optimal implant selection requires careful consideration of the patient-specific factors, implant design, and surgical technique. Understanding the biomechanical behavior of implant–tissue interactions is crucial for achieving successful and long-lasting implant therapy. To adequately address this issue and improve the rigorous selection criteria from a biomechanically numerical approach, this research aims to analyze the stress distribution fields, strain patterns, and load transfer displacements within the implant system and the implant–biological interface (gingival and bony tissues) of titanium three-piece to two–one-piece ceramic implant systems. Thus, three different commercially available dental implants designed to be placed in the jaw molar region were considered for evaluation through the finite element method under both oblique and occlusal loading conditions. The results have exhibited an increasing trend to highlight the outstanding behavior of two-piece ceramic implants to dissipate the stress distribution better (6 and 2 times lower than the three- and one-piece systems under occlusal loads and almost 5 and 1.3 times more efficient for oblique loading, respectively), minimize peak stress values (below 100 MPa), and reduce strain peak patterns compared with the other two evaluated designs. On the other hand, the effects generated in biological tissues are strongly associated with implant geometry features. This biomechanical approach could provide a promising strategy for predicting micro-strains and micromotion in implant system pieces and geometries. Hence, these findings contribute to a deeper understanding of the biomechanics spectrum in the behavior of dental implant systems and emphasize the importance of carefully selecting appropriate material systems for accurate patient-specific biomechanical performance.